Early mesolithic technical systems of Southern France and Northern Italy - Visentin, Davide (Archaeopress Publishing Ltd, 2018)
The Sauveterrian represents one of the main cultural aspects of the European Early Mesolithic. In this work, its presumed uniformity - mostly based on typological grounds - is questioned with the purpose of assessing and verifying the relationships existing between the two central areas of diffusion of this complex: southern France and northern Italy. A broad technological approach, combining complementary analytical techniques, was applied to the study of a series of French and Italian lithic assemblages. More specifically, these were investigated with the aim of reconstructing the entire reduction sequences, from the procurement of lithic raw materials to the use and discard of tools.